EXAMINING ‘SITA’ THROUGH THE ARTISTIC KALEIDOSCOPE OF RAJA RAVI VARMA AS AN EXPRESSION OF GENDER STEREOTYPE - PS, Sethulekshmi; Selvarajan, Saraswathy (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The word myth originated from the Greek word ‘mythos’ meaning story or tale. Etymologically, the word cues the oral tradition which introduces the socio-cultural heritage of the country. Myth and legends are popular and widely incorporated themes in Indian art and tradition. Colonial Indian artist, Raja Ravi Varma’s paintings are based on the mythological instances mentioned in the epics like Ramayana and Mahabharata. His paintings of God and Goddess are significant in popularising Hindu mythology among the people irrespective of caste and class. Fused with Western art techniques and Indian sensibilities the works of Raja Ravi Varma reflect the social-cultural norms of the time. Thus, through the select works of Varma based on Ramayana, this work studies how Sita is portrayed in connection with gender norms.